2021
DOI: 10.1098/rsif.2021.0326
|View full text |Cite
|
Sign up to set email alerts
|

Knee extension moment arm variations relate to mechanical function in walking and running

Abstract: The patellofemoral joint plays a crucial mechanical role during walking and running. It increases the knee extensor mechanism's moment arm and reduces the knee extension muscle forces required to generate the extension moment that supports body weight, prevents knee buckling and propels the centre of mass. However, the mechanical implications of moment arm variation caused by patellofemoral and tibiofemoral motion remain unclear. We used a data-driven musculoskeletal model with a 12-degree-of-freedom knee to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 56 publications
(72 reference statements)
0
3
0
Order By: Relevance
“…Studies have shown that during the running cycle, the tibia is impacted, and the knee exion angle increases at the moment of foot strike and during the off-ground phase of each run. When muscles are subjected to prolonged repetitive loading, the strength of the hamstrings and quadriceps decreases, leading to increased tibial inversion rotation, femoral translation, and increased risk of KOA [30][31][32] . Another important cause of KOA may be changes in knee cartilage caused by prolonged loading.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that during the running cycle, the tibia is impacted, and the knee exion angle increases at the moment of foot strike and during the off-ground phase of each run. When muscles are subjected to prolonged repetitive loading, the strength of the hamstrings and quadriceps decreases, leading to increased tibial inversion rotation, femoral translation, and increased risk of KOA [30][31][32] . Another important cause of KOA may be changes in knee cartilage caused by prolonged loading.…”
Section: Discussionmentioning
confidence: 99%
“…The patella functions as an articulating fulcrum, enhancing the moment arm of the extensor mechanism. Additionally, it enhances quadriceps muscle efficiency by elevating the extensor mechanisms away from the axis of rotation of the knee, thus increasing torque ( Wheatley et al, 2021 ). Moreover, it assists in reducing frictional wear that could otherwise damage the extensor mechanism tendon.…”
Section: Introductionmentioning
confidence: 99%
“…X-ray Reconstruction of Moving Morphology (XROMM) has permitted biologists and biomechanists to visualize and measure in vivo musculoskeletal movement and ex vivo capacities of an organism with precision and accuracy (e.g., Brainerd et al 2010 ; Gatesy et al 2010 ; Nyakatura and Fischer 2010 ; Stefen et al 2011 ; Baier and Gatesy, 2013 ; Arnold et al 2014 ; Kambic et al 2014 ; Nyakatura et al 2014 ; Camp et al 2015 ; Brainerd et al 2016 ; Panagiotopoulou et al 2016 ; Brocklehurst et al 2017 ; Kambic et al 2017 ; Fischer et al 2018 ; Capano et al 2019 ; Bhullar et al 2019 ; Nyakatura et al 2019 ; van Meer et al 2019 ; Manafzadeh 2020 ; Tsai et al 2020 ; Turner et al 2020 ; Bishop et al 2021a ; Jones et al 2021 ; Manafzadeh and Gatesy 2021 ; Manafzadeh et al 2021 ; Wiseman et al 2021 ; Turner and Gatesy 2021 ; Wheatley et al 2021 ; Regnault et al 2021 ). XROMM captures movement data using biplanar X-ray videos, which is then integrated with 3D scan data consisting of skeletal elements of the same specimen.…”
Section: Introductionmentioning
confidence: 99%
“…The method (scientific rotoscoping versus IK solvers) should reflect the research goals. For example, biomechanical studies using musculoskeletal models to investigate parameters such as joint moments, moment arms, and/or muscular mechanics typically only include three DOFs at the most proximal joint, with all distal joints typically composed of a single DOF; just flexion–extension (see: Delp et al 1990 ; Seth et al 2016 ; Wiseman et al 2021 ; Bishop et al 2021a , 2021b ; but also see: Kambic et al 2014 ; Wheatley et al 2021 ). This is in contrast to other studies investigating range of motion around a given joint whereby all six DOFs are preferential (i.e., Manafzadeh and Gatesy 2021 ) and are incorporated into scientific rotoscoping approaches, but not in IK solver approaches.…”
Section: Introductionmentioning
confidence: 99%